Conversations that count in online student engagement – a case study - Jin, Y; Rowan, L (https://publications.ascilite.org/index.php/APUB/article/view/162, 2022)
A challenge all teachers face is how to engage students meaningfully in their learning. The impact of Covid has made online learning in higher education more prevalent. While many students and teachers have readily adjusted to these new learning environments others have found the shift difficult. To enable students’ adjustment to new ways of learning teachers and course designers should consider approaches which encourage and support positive experiences and attitudes towards online learning. Students’ participation and engagement grows when good course design and a variety of learning activities are used and conveyed to them in clear communication that guides their learning processes. This case study looks at one teacher’s intentions and actions to improve student engagement within a health science core course through collecting ‘student voice’, students’ perspectives of what helped their learning and what could be improved to enhance their learning online.
Keywords: student engagement; student voice; learning interactions